ANÁLISIS DEL BIENESTAR SUBJETIVO EN ECUADOR, PERIODO 2007-2009 - Paladines Ramírez, Jomaira Patricia (2016)
The present investigation study the main contributions of the so-called “happiness economics” , in order to compare the main hypothesis of this analytical framework. At this level, based on the apparent empirical relationship observed income-happiness relationship was proposed a comprehensive model with greater explanatory capability that integrates socio-economic and perceptual variables. The main objective of this research is the measure the subjective well-being in Ecuador from the analysis of the degree of satisfaction that people perceive of the environments which shape their lives, in contrast with main socioeconomic variables and family structure of households in the period 2007-2009. The main theoretical approaches discussed are geography, culture, subjective well-being, socio-economic variables, happiness state of people, the Easterlin paradox and the explanatory variables of people who consider themselves as "very happy" or "very unhappy". The methodology used was the application of “ordered logit” and “dichotomous logit” models using statistical programs like Stata 9.1. This type of econometric models were constructed from the national survey of employment, unemployment and underemployment (ENEMDU), which provided important evidence about the determinants of happiness in the socioeconomic environment of Ecuadorian people. The results show that the favorable trend of subjective well-being goes beyond income growth, rather is due to another perceptual variables like “family”, “leisure”, “social relationships with the community”, “health”, “personal freedom” and “personal values”; in other words, such variables significantly determine the level of welfare of Ecuadorian people; therefore, in this research was performed a deep analysis of perception and socioeconomic variables that generate greater happiness. It was also characterized the distribution of happiness by province and influential variables within the group of Ecuadorians who define themselves as "very happy" and "very unhappy"